Level of Educational Programs Provided to Students with Disabilities at the Academy of Tayeb Ali Taha in Kosti City - Awadallah Mohammed Abuelgassim; Hanadi Eassa Mohana (University of Science and Technology, Yemen, 2020)
The study aimed to identify the level of effectiveness of educational programs provided to students with disabilities at the Academy of Tayeb Ali Taha in Kosti, in light of the international standards of special education. The researchers used the descriptive correlational method. To collect data, indicators of the international standards of special education, which include strategic planning, educational administration, educational environment, educational programs, family participation, integration and transition services, and evaluation, were applied. The indicators were used with a purposive sample of (34) employees of Al Tayeb Ali Academy for Special Needs. The SPSS software was used for data analysis. Major results revealed a low level of effectiveness of the programs presented in light of the international standards of education with a mean of (2.28) at the level of statistical significance (0.05). Findings also revealed significant differences at the level of significance (0.05) and a mean of (41.83), which indicates the highest level of effectiveness. The mean of effectiveness of the educational environment dimension was (37.166); the dimension of administration and workers scored a low medium mean of (27.25); and the dimension of integration and transition services scored a mean of (25 33). The lowest level of effectiveness of the dimensions: the participation of the family scored a mean of (16.58), and the strategic planning scored a mean of (19.50). The study recommended preparing trained teams to evaluate the effectiveness of the standards for the different programs and services provided to students with disabilities in the "White Nile State", implementing accountability system, and rolling out the criteria and indicators adopted by the Council of Persons with Disabilities to all institutions in the state.  Keywords: educational programs, the disabled, international standards of special education